IMPLEMENTASI HADIS CAMBUK DI ACEH DAN RELEVANSINYA TERHADAP QANUN ACEH: - Munir, Fitri Wardani (Al-Bukhari : Jurnal Ilmu Hadis, 2019)
Aceh is a majority of Muslim  always be a discussion which was discussed by academics, researcher, and also historian. One of factor in backs is  because Aceh is the only city officially establish Islamic science in daily activity. This execution is marked by the imposition of a canning sentence to violator of Islamic rules and also the Aceh?s culture. But, how the implementation of the canning punishment in Aceh and how is the relation with Aceh?s Q?n?n? And also how the implementation of canning punishment which refers to the hadith about the canning punishment to the all adulterer both men and women? And what is the background of Aceh?s government to establish the canning punishment? In this case many people oppose to this punishment, because this punishment considered human rights abuses. In fact, establish Islam rules in Aceh is not chopping the human rights, which is agreed upon by the authorities.